2015
DOI: 10.1118/1.4908203
|View full text |Cite
|
Sign up to set email alerts
|

3D high spectral and spatial resolution imaging of ex vivo mouse brain

Abstract: Purpose: Widely used MRI methods show brain morphology both in vivo and ex vivo at very high resolution. Many of these methods (e.g., T 2 * -weighted imaging, phase-sensitive imaging, or susceptibility-weighted imaging) are sensitive to local magnetic susceptibility gradients produced by subtle variations in tissue composition. However, the spectral resolution of commonly used methods is limited to maintain reasonable run-time combined with very high spatial resolution. Here, the authors report on data acquisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 85 publications
(83 reference statements)
4
19
0
Order By: Relevance
“…This arises from myelin's unique chemical composition and ordering of phospholipids within the myelin sheath structure. Following empirical works demonstrating that the frequency dependent MR signal (e.g., spectroscopic imaging) may reflect localized differences in magnetic susceptibility v (7)(8)(9), recent studies have shown that the magnetic susceptibility of myelin strongly influences the gradient echo (GRE) signal, including both signal phase and magnitude (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…This arises from myelin's unique chemical composition and ordering of phospholipids within the myelin sheath structure. Following empirical works demonstrating that the frequency dependent MR signal (e.g., spectroscopic imaging) may reflect localized differences in magnetic susceptibility v (7)(8)(9), recent studies have shown that the magnetic susceptibility of myelin strongly influences the gradient echo (GRE) signal, including both signal phase and magnitude (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The highest spatial resolution currently achieved for ex vivo MRI imaging of a brain is around 50–100 μm when using extremely high field strengths on the order of 9–16 T 10 (for reference, clinical CT scanners operate up to 3 T). The best in vivo MRI resolution achieved to date is 100 μm using 7.00–11.7 T scanners 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, the number of PRESS spectra acquired over the mammary gland was small; future studies should include denser sampling of the mammary glands at high spectral resolution. Third, the spectral resolution and spectral bandwidth of HiSS data sets was modest; in future studies HiSS sampling methods will be improved to acquire data at higher spectral resolution with an acceptable run time, and to sample early echoes with shorter readout gradients in order to improve detection of short T2* signals [ 33 ]. Finally, these high fat and high fructose diets did not perfectly model Western diets.…”
Section: Discussionmentioning
confidence: 99%